Analysis of Barriers to Implementation of the Independent Curriculum Study the Merdeka Campus in the Department Economic Education Manado State University - Palangda, Listriyanti; Naharia, Orbanus; Sumual, Shelty D M; Ebe, Lord Steward; Mandey, Larry (International Journal of Multidisciplinary Approach Research and Science, 2023)
Universities are required to be able to adjust to existing education with the current state of the Indonesian industry. Merdeka Learning Merdeka Campus (MBKM) is a policy of the Minister of Education and Culture which encourages students to master various knowledge as subjects before entering the world of business and industry. The purpose of this study was to analyze the obstacles faced by economics education majors in implementing the independent campus learning curriculum (MBKM). This type of research is quantitative. The data collection technique in this study was carried out by identifying discourse from MBKM documents, scientific articles in national and international journals, Ministerial Regulations and Legislation, as well as other online literature. The stages of the research included data collection, data analysis, and obtained the results and conclusions of the obstacles faced in the implementation of MBKM in the Department of Economic Education Reputable.